Impact of climate change on stakeholder's' perspectives towards diving and snorkeling : a case study ofSimilan islands National Park, Phang-Nga Province - Sijittra Songcharoen (Prince of Songkla University, 2015)
Thesis (M.B.A. (Hospitality and Tourism Management (International Program)))--Prince of Songkla University, 2014